1998
DOI: 10.1071/wr95066
|View full text |Cite
|
Sign up to set email alerts
|

The performance of wild-canid traps in Australia: efficiency, selectivity and trap-related injuries

Abstract: Wild dogs and European red foxes are considered pest animals in Australia. Restraining devices to capture these wild canids are sometimes required by wildlife managers. However, the use of traps is controversial. This paper discusses the efficiency, selectivity and injuries inflicted by some leg-hold traps that are available in Australia for capturing wild canids. The trapping of feral cats with wild-canid traps is also briefly discussed. The most commonly used leg-hold trap in Australia is the toothed, steel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…In France, Ruette et al (2003) obtained efficiencies of 1.2-17.9 foxes per 1,000 trap-nights and 0-31.7 foxes per 1,000 trap-nights, using neck or leg snares, respectively. Efficiencies calculated for Australia and US using different kind of snares varied from a minimum of 2.1 to as much as 21.6 foxes per 1,000 trap-nights (Litvaitis et al 1984, Meek et al 1995, Bubela et al 1998, Fleming et al 1998, Shivik et al 2005. Efficiency obtained in this study falls within the ranged observed by other authors in Europe using similar devices.…”
Section: Discussionsupporting
confidence: 79%
“…In France, Ruette et al (2003) obtained efficiencies of 1.2-17.9 foxes per 1,000 trap-nights and 0-31.7 foxes per 1,000 trap-nights, using neck or leg snares, respectively. Efficiencies calculated for Australia and US using different kind of snares varied from a minimum of 2.1 to as much as 21.6 foxes per 1,000 trap-nights (Litvaitis et al 1984, Meek et al 1995, Bubela et al 1998, Fleming et al 1998, Shivik et al 2005. Efficiency obtained in this study falls within the ranged observed by other authors in Europe using similar devices.…”
Section: Discussionsupporting
confidence: 79%
“…1995). Bubela, Bartell & Müller (1998) recorded 0·025–0·026 captures trap‐night −1 for treadle snares, and Fleming et al . (1998) 0·016–0·056 captures trap‐night −1 for a variety of methods.…”
Section: Discussionmentioning
confidence: 90%
“…These traps are designed to reduce impact on the captured animal's limb (see Meek et al, 1995;Fleming et al, 1998). In each study area traps were set on or adjacent to vehicular trails at sites with wild dog scratchings, urine stains or faeces.…”
Section: Trapping Methodologymentioning
confidence: 99%